'Where am I in the text?' Standing with Refugees in Graphic Narratives - Jena Habegger-Conti (CLELEjournal, 2021)
This article contributes to current research on the use of graphic narratives for intercultural education with young adult learners in English Language Teaching. The article focuses on When Stars are Scattered by Victoria Jamieson and Omar Mohamed (2020).